Tourism Promotion Video of Gundaling Berastagi Using Vintage Effects - Sitepu, Paulina; Diningrat, Raden Burhan Surya Nata; Azis, Adek Cerah Kurnia; Yumielda, Vivi Destri (V-art: Journal of Fine Art, 2024)
Berastagi is a popular tourist town in North Sumatra that introduces the Gundaling tourism site. However, the town remains relatively unknown to the wider public due to a lack of information and digital promotion. This study aims to create a tourism promotion video for the Gundaling destination in Berastagi, using vintage effects as a key component to create visual and emotional appeal for the audience. The use of vintage effects, such as vintage filters, soft color gradation, and classic lighting, creates a nostalgic atmosphere that can attract visitors and present Gundaling as a tourist destination offering historical and cultural value in addition to its natural beauty. The video production follows the MDLC (Multimedia Development Life Cycle) method, resulting in 12 promotional video pieces. The use of vintage effects in these promotional videos successfully enhances emotional appeal, strengthens Gundaling's visual identity, and broadens audience reach. It is hoped that this promotional video will help make Gundaling stand out among other tourist destinations by enhancing visual appeal and the overall visitor experience.